Large Bowel Obstruction, a Delayed Complication of Severe Gallstone Pancreatitis. (26th October 2016) - Lal, Neeraj; Whiting, John; Hejmadi, Rahul; Raman, Sudarsanam
Abstract : Colonic complications are rare after acute pancreatitis but are associated with a high mortality. Possible complications include mechanical obstruction, ischaemic necrosis, haemorrhage, and fistula. We report a case of large bowel obstruction in a 31-year-old postpartum female, secondary to severe gallstone pancreatitis. The patient required emergency laparotomy and segmental bowel resection, as well as cholecystectomy. Presentation of obstruction occurs during the acute episode or can be delayed for several weeks. The most common site is the splenic flexure owing to its proximity to the pancreas. Initial management may be conservative, stenting, or surgical. CT is an acceptable baseline investigation in all cases of new onset bowel obstruction. Although bowel obstruction is a rare complication of pancreatitis, clinicians should be aware of it due to its high mortality. Obstruction can occur after a significant delay following the resolution of pancreatitis. Those patients with evidence of colonic involvement on pancreatic imaging warrant further large bowel evaluation. Bowel resection may be required electively or acutely. Colonic stenting has an increasing role in the management of large bowel obstruction but is a modality of treatment that needs further evaluation in this setting.